Apoferritin delivery of imidazotetrazine agents for targeted brain tumour therapy - Bouzinab, Kaouthar (2021)
Glioblastoma multiforme (GBM) is an aggressive grade IV astrocytoma. The standard of care for GBM includes surgery, radiotherapy and temozolomide (TMZ; DNA alkylating) chemotherapy. Poor TMZ accumulation at the tumour site, resistance and toxicity, limit the success of this treatment. Some modes of TMZ resistance includes drug efflux by P-glycoprotein 1 (Pgp), overexpression of O6-methylguanine DNA-methyltransferase (MGMT; removes cytotoxic O6-methylated guanine (O6-MeG) lesions), deficiency in base excision repair (BER; e.g. poly (ADP-ribose) polymerase (PARP); removes N7-methylguanine (N7-MeG) and N3-methyladenine (N3-MeA) lesions)) and/or deficiency in mismatch repair (MMR; leads to tolerance of O6-MeG lesions).